2022
DOI: 10.3390/separations9120444
|View full text |Cite
|
Sign up to set email alerts
|

Application of O3/PMS Advanced Oxidation Technology in the Treatment of Organic Pollutants in Highly Concentrated Organic Wastewater: A Review

Abstract: The ozone/peroxymonosulfate (O3/PMS) system has attracted widespread attention from researchers owing to its ability to produce hydroxyl radicals (•OH) and sulfate radicals (SO4•−) simultaneously. The existing research has shown that the O3/PMS system significantly degrades refinery trace organic compounds (TrOCs) in highly concentrated organic wastewater. However, there is still a lack of systematic understanding of the O3/PMS system, which has created a significant loophole in its application in the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Integrated ozone-based AOPs are more effective than ozone alone in the removal of organic compounds [25]. Yan et al [26] stated that the ozone/peroxymonosulfate (O 3 /PMS)-based technique has a high potential in the treatment of organic wastewater effluents; their investigation found that 85.6% of COD, 81.7% of chromaticity, and 77.6% of dissolved organic carbon (DOC) were removed. Another study found that >49% of alachlor, as an emerging contaminant, was removed by ozone/hydrogen peroxide (O 3 /H 2 O 2 ) [27].…”
Section: Treatment Challenges Of Water and Wastewatermentioning
confidence: 99%
“…Integrated ozone-based AOPs are more effective than ozone alone in the removal of organic compounds [25]. Yan et al [26] stated that the ozone/peroxymonosulfate (O 3 /PMS)-based technique has a high potential in the treatment of organic wastewater effluents; their investigation found that 85.6% of COD, 81.7% of chromaticity, and 77.6% of dissolved organic carbon (DOC) were removed. Another study found that >49% of alachlor, as an emerging contaminant, was removed by ozone/hydrogen peroxide (O 3 /H 2 O 2 ) [27].…”
Section: Treatment Challenges Of Water and Wastewatermentioning
confidence: 99%
“…Several approaches have been introduced within the past 2 decades focusing on the treatment of organics-contaminated wastewater, and the common method in the current applications is chemical oxidation (Asghar et al, 2015;Sun et al, 2015). Among other chemical oxidation processes, AOP is categorized to be a versatile approach in wastewater technology due to the in situ formation of reactive oxygen species (ROS) such as hydroxyl radicals (OH•) (Yan et al, 2022;Yasasve et al, 2022;Aljedaani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%